Ageing Tests on Gold Layers and Bonded Contacts. (1977) - Hieber, H.; Betke, F.; Pape, K.
Abstract : Studies have been made of the adhesion of gold thin films on NiCr and Mo layers deposited on ceramic substrates. It is shown that the ageing behaviour and the related long-term adhesion losses are complex processes and the various contributing mechanisms are identified.